The impact of home farming and digital platforms on food sustainability in the UAE: Stakeholder perspectives - Zainudin, Mohamad Zahir; Eissa, Mouza Mohammed; Ahmat, Norun Najjah (Macrothink Institute, 2025)
The United Arab Emirates (UAE) faces persistent food security challenges due to its hyper-arid climate, scarce natural resources, and heavy dependence on food imports. This qualitative study examines pathways to strengthen food sustainability through home farming, innovative agricultural methods, and digital platforms, aligning with the National Food Security Strategy 2051. Semi-structured interviews were conducted with 35 stakeholders including home farmers, commercial producers, policymakers, and agritech developers which to identify barriers, opportunities, and policy gaps. Findings reveal that 70% of home farmers engage in urban agriculture to reduce import dependency but are constrained by high water costs (70%) and limited technical training (55%). Commercial farms widely implement hydroponics (88%) and vertical farming (62%), yet energy-water trade-offs hinder scalability. Stakeholders emphasized the potential of AI-driven tools to optimize water use (75%) and blockchain applications (45%) for improved traceability. The most desired digital platform features include real-time soil and weather data (90%), centralized subsidy access (80%), and market linkages (65%), although fragmented data systems currently limit effectiveness. Policy implementation gaps persist, with 60% of farmers unaware of subsidy programs and minimal integration across agricultural initiatives. The study recommends expanding solar-powered irrigation subsidies, improving training and extension services, and developing a unified digital platform to connect farmers, policymakers, and agritech stakeholders. By bridging grassroots innovation with national strategy, the UAE can enhance climate resilience, resource efficiency, and progress toward its 2051 goal of global leadership in sustainable food security.